2011
DOI: 10.1111/j.1398-9995.2011.02668.x
|View full text |Cite
|
Sign up to set email alerts
|

Markers of autoreactivity, coagulation and angiogenesis in patients with nonallergic asthma

Abstract: Nonallergic asthma is characterized by autoreactivity as well as increased coagulation and angiogenesis markers, which are known to enhance vascular permeability. The presence of circulating vasoactive factors may be relevant to understand the disease pathophysiology and to detect novel therapeutic strategies in nonallergic asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…On the other hand, our findings concerning D‐dimer evaluation confirmed previous studies showing increased D‐dimer levels in non‐allergic asthma . However, the current findings were conflicting with other studies that reported negative outcomes.…”
supporting
confidence: 61%
“…On the other hand, our findings concerning D‐dimer evaluation confirmed previous studies showing increased D‐dimer levels in non‐allergic asthma . However, the current findings were conflicting with other studies that reported negative outcomes.…”
supporting
confidence: 61%
“…Patients with severe asthma demonstrated increased soluble TF in induced sputum as compared to moderate asthma or healthy subjects [9]. Asero et al [10] showed higher plasma prothrombin fragments 1 + 2 and D-dimer in asthma subjects, suggesting marked activation of blood coagulation. Animal studies yielded further evidence supporting the concept of involvement of coagulation proteins in the pathogenesis of asthma.…”
Section: Introductionmentioning
confidence: 98%
“…If sodium citrate were able to induce nonspecific weal‐and‐flare reactions as claimed by Yıldız et al. , one would expect to find a large prevalence of normal subjects scoring positive on APST but, again, this has never been observed in our series 2–4 as well as by other authors 5 . In the original paper published in the Journal of Allergy and Clinical Immunology , 2 to assess the specificity of skin reactions induced by autologous plasma, 10 patients [five positive on autologous serum skin test (ASST) and eight on APST] underwent further intradermal tests using sodium citrate 0·125 mol L −1 in saline; no patient reacted to this solution.…”
mentioning
confidence: 50%